Los erizos Arbacia incisa y Eucidaris thouarsii (Echinodermata) como agentes de biocontrol del “fouling” en canastas de cultivo de Crassostrea gigas (Mollusca: Ostreidae) - Sonnenholzner, Jorge (2017)
The sea urchins Arbacia incisa and Eucidaris thouarsii (Echinodermata) as fouling biocontrol agents in culture cages of Crassostrea gigas (Mollusca: Ostreidae).Fouling clogs cultivation cages of bivalves afecting their growth. We tested biocontrol with sea urchins in the suspended culture of C. gigas during one month. The experimental design included: 1) oysters without sea urchins, 2) oysters with the black sea urchin Arbacia incisa (50.5 ± 0.43 mm of diameter testa-DT), 3) oysters with the pencil sea urchin E. thouarsii (34. 2 ± 2.13 mm DT) and 4) oysters without sea urchins with a pearl net protective bag (to avoid predation). The dry mass of the pearl nets and the oyster soft tissues were determined at the beginning and end of the experiment. There was similar fouling in cages without urchins (55.3 ± 5.80 g) and with A. incisa (46.1 ± 2.84 g). These amounts were significantly higher than those found in cages with E. thouarsii (39.1 ± 1.9 g) and with protective sacs without urchins (35.6 ± 5.17 g). The growth of C. gigas with E. thouarsii was significantly higher (0.49 ± 0.089 g). We recommend E. thouarsii as a fouling biocontrol agent for C. gigas. Rev. Biol. Trop. 65(Suppl. 1): S35-S41. Epub 2017 November 01.